2021
DOI: 10.3389/fneur.2021.736115
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Movements in Acquired Neurological Disorders: A Mini-Review

Abstract: Mirror movements (MMs) are specifically defined as involuntary movements occurring on one side of homologous muscles when performing unilateral movements with the contralateral limb. MMs have been considered a kind of soft neurological signs, and the persistence or reappearance of MMs in adults is usually pathologic. In addition to some congenital syndrome, MMs have been also described in age-related neurological diseases including pyramidal system diseases (e.g., stroke, amyotrophic lateral sclerosis) and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…[20][21][22][27][28][29] Regarding acquired neurological diseases, MM have been described mainly in pyramidal syndromes (in amyotrophic lateral sclerosis and in non-paretic limbs of patients with hemiplegic stroke), in parkinsonian syndromes, in essential tremor and in Huntington's disease. 20,21 In Parkinson's disease (PD) patients,…”
Section: Mirror Movementsmentioning
confidence: 99%
See 3 more Smart Citations
“…[20][21][22][27][28][29] Regarding acquired neurological diseases, MM have been described mainly in pyramidal syndromes (in amyotrophic lateral sclerosis and in non-paretic limbs of patients with hemiplegic stroke), in parkinsonian syndromes, in essential tremor and in Huntington's disease. 20,21 In Parkinson's disease (PD) patients,…”
Section: Mirror Movementsmentioning
confidence: 99%
“…[34][35][36][37] Differently from PD, in cortico-basal syndrome (CBS) patients, MM have been usually described in the most affected hand. 20,21 There is not a definitive explanation for the different hand involvement in these two parkinsonian syndromes. Some authors hypothesized that MM might be more evident in the less affected side in PD patients due to the lower degree of rigidity and bradykinesia 34 ; however, this explanation would not fit the case of CBS patients.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found a correlation between the performance of MMs and the patient’s motor function ( Kim et al, 2003 ; Hwang et al, 2005 ). Furthermore, MMs persist if the patient has a poor functional prognosis ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%